WLE/IWMI support for updated groundwater policies and implementation programs in Laos has led to new policies and investments in sustainable groundwater management - CGIAR Research Program on Water, Land and Ecosystems (2021)
WLE/IWMI support for updated groundwater policies and implementation programs in Laos has led to new policies, investments and capacity development in sustainable, integrated groundwater management